PENINGKATAN HASIL BELAJAR IPS MELALUI METODE CARD SORT SISWA KELAS VIIB DI SMP NEGERI 3 KAMPAK - Arini, Trisia (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2020)
The purpose of this study was to determine the level of student learning effectiveness through the Card Sort method in Social Science (IPS) subjects. Social studies subjects are one of the compulsory subjects for junior high school (SMP) students. Social studies is a subject that must be mastered by students because the material content is very important. However, it is unfortunate that many students do not have a high interest in social studies subjects. Apart from the material that requires a lot of memorization, conventional teacher learning methods also make students even more bored. By using Classroom Action Research (CAR) and through the data validation stage, the results of this study showed the value of learning outcomes and the level of student learning completeness were much higher than using conventional methods.